2021
DOI: 10.21203/rs.3.rs-144669/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions for Improving Outcomes in Patients With Multimorbidity in Primary Care and Community Setting: A Systematic Review

Abstract: BackgroundMultimorbidity, defined as the co-existence of two or more chronic conditions, presents significant challenges to patients, healthcare providers and health systems. Despite this, there is ongoing uncertainty about the most effective ways to manage patients with multimorbidity. This review aimed to determine the effectiveness of interventions designed to improve outcomes in people with multimorbidity in primary care and community settings, compared to usual care.MethodsWe searched eight databases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The term "multimorbidity" -which at times has been used interchangeably with comorbidity -has been defined by many different criteria -most commonly as two or more conditions [18], but also as one of 40 chronic diseases [19], one of 918 ICD-10 disease groups grouped Psychother Psychosom 2022;91:145-151 DOI: 10.1159/000521952 into 60 categories [20], two of 28 diseases [21], treatment with multiple medications [17], impaired quality of life or function [22] and/or physical and mental disorders [19]. The lack of a standard definition vastly complicates the interpretation and use of multimorbidity [18,[23][24][25].…”
Section: The Elements In Comorbidity Assessmentsmentioning
confidence: 99%
“…The term "multimorbidity" -which at times has been used interchangeably with comorbidity -has been defined by many different criteria -most commonly as two or more conditions [18], but also as one of 40 chronic diseases [19], one of 918 ICD-10 disease groups grouped Psychother Psychosom 2022;91:145-151 DOI: 10.1159/000521952 into 60 categories [20], two of 28 diseases [21], treatment with multiple medications [17], impaired quality of life or function [22] and/or physical and mental disorders [19]. The lack of a standard definition vastly complicates the interpretation and use of multimorbidity [18,[23][24][25].…”
Section: The Elements In Comorbidity Assessmentsmentioning
confidence: 99%
“…[1][2][3][4]6,7 The evidence base for how best to treat patients with multimorbidity is very limited, and most interventions to date have not been evaluated or demonstrated effectiveness or cost-effectiveness. 8 It is widely accepted that interventions in multimorbidity are likely to be complex, 9 and expert guidelines exist on the development and evaluation of complex interventions. 9,10 A recent Delphi study funded by the MRC-NIHR Methodology Research Panel also reached a consensus that theory is a crucial part of developing complex interventions and concluded that a theory-driven approach to intervention development and evaluation is more likely to be effective than a purely pragmatic or empirical approach.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence base for how best to treat patients with multimorbidity is very limited, and most interventions to date have not been evaluated or demonstrated effectiveness or cost‐effectiveness 8 . It is widely accepted that interventions in multimorbidity are likely to be complex, 9 and expert guidelines exist on the development and evaluation of complex interventions 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed in studies with Spanish patients that those who use primary care the most are multimorbid people (3,4). This supposes significant challenges for health systems (8,9). It has been considered to increase mortality, decrease quality of life (10,11), and increase costs and negative consequences for patients (12,13).…”
Section: Introduction Chronic Conditions and Multimorbiditymentioning
confidence: 99%